2021
DOI: 10.3390/metabo11020094
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Di-(2-ethylhexyl)phthalate and Di-(2-ethylhexyl)terephthalate Metabolites on Thyroid Receptors: In Vitro and In Silico Studies

Abstract: Plasticizers added to polyvinylchloride (PVC) used in medical devices can be released into patients’ biological fluids. Di-(2-ethylhexyl)phthalate (DEHP), a well-known reprotoxic and endocrine disruptor, must be replaced by alternative compounds. Di-(2-ethylhexyl) terephthalate (DEHT) is an interesting candidate due to its lower migration from PVC and its lack of reprotoxicity. However, there is still a lack of data to support the safety of its human metabolites with regard to their hormonal properties in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…The differences in the two studies may be due to the two different molecular docking platforms used. However, our results on molecular docking of DEHP are supported by the results from this former study for DEHP metabolites [ 46 ]. Further, using a T-screen assay—a thyroid hormone-dependent rat pituitary tumor cell growth assay—Kambia et al reported that MEHP and 5-OH-MEHP induced concentration dependent agonist activity in the cells stimulating cell growth, which was synergically enhanced by the addition of T3 [ 46 ]; however, 5-oxo-MEHP showed antagonistic and cytotoxic activity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The differences in the two studies may be due to the two different molecular docking platforms used. However, our results on molecular docking of DEHP are supported by the results from this former study for DEHP metabolites [ 46 ]. Further, using a T-screen assay—a thyroid hormone-dependent rat pituitary tumor cell growth assay—Kambia et al reported that MEHP and 5-OH-MEHP induced concentration dependent agonist activity in the cells stimulating cell growth, which was synergically enhanced by the addition of T3 [ 46 ]; however, 5-oxo-MEHP showed antagonistic and cytotoxic activity.…”
Section: Discussionsupporting
confidence: 88%
“…Phthalate plasticizers, especially DEHP, have been shown to affect the hypothalamic-pituitary-thyroid axis and perturb the thyroid hormone homeostasis in epidemiological studies in humans [ 42 , 45 ] and in experimental laboratory animal and in vitro studies [ 40 , 46 , 47 ]. Alternative plasticizers are increasingly replacing phthalates in commercial and household products, such as food packaging, medical devices, cosmetic products, sealants, carpet, plastic tubing, fabrics, children’s toys, vinyl flooring, and several other applications [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there were some questions raised relating to variations and reduced fetal weights secondary to decreased maternal food consumption; however, such effects need to be evaluated according to the respective OECD evaluation guidelines [ 24 ]. Interestingly, while this publication was submitted to the journal on 22 March 2021, several co-authors of L. Bernard recognized already on 29 November 2020, when submitting the publication by Kambia et al, 2021 [ 25 ], the lack of reproductive toxicity of DEHT, stating: “Di-(2-ethylhexyl) terephthalate (DEHT) is an interesting candidate due to its lower migration from PVC and its lack of reprotoxicity”.…”
Section: Commentsmentioning
confidence: 99%
“…This is similar to a study in Australian(Bai et al, 2015), slightly higher total phthalate metabolite concentration were associated with insu cient activity.Normal thyroid function is important in maintain normal reproduction, and could be impacted by the endocrine disrupting effects of PAEs(Krassas et al, 2010). Recent studies in animals(Dong et al, 2019) and in vitro(Kambia et al, 2021) screening assays provide evidence that phthalate exposure might affect fetal neurodevelopment through thyroid signaling mechanisms. Our results showed that MEP and MBzP were negatively associated with FT4 and FT3.…”
mentioning
confidence: 99%